Restaurants' motivations to solicit fake reviews: A competition perspective. (October 2022) - Zhang, Ziqiong; Li, Yuanshuo; Li, Hengyun; Zhang, Zili
Abstract: As restaurants increasingly solicit fake reviews on online word-of-mouth (WOM) platforms, the authenticity and credibility of online reviews have been compromised. This study investigates restaurants' motivations to solicit positive fake reviews from a competition perspective. Our results show that a higher number of positive fake reviews by competitors can more strongly motivate a restaurant to solicit positive fake reviews, whereas a market advantage over competitors (based on review valence) significantly reduces a restaurant's motivation to solicit positive fake reviews. Furthermore, the extent of the above two effects is moderated by the degree of prospective popularity; no significant difference was observed between chain and independently owned restaurants. Theoretical and practical implications of these findings are also discussed. Highlights: This study investigates restaurants' motivations to solicit positive fake reviews from a competition perspective. Competitors' aggressive solicitation of fake reviews can enhance a restaurant's motivation to solicit more fake reviews. A stronger market advantage can reduce a restaurant's motivation to solicit positive fake reviews. Prospective popularity can strengthen a restaurant's motivation to solicit positive fake reviews. No significant differences exist between chain and independent restaurants in motivations to solicit positive fake reviews.